USG Pengganti Hukum Iddah Perspektif Maqashid Syari'ah - rahmad achri subri (AL-FIKRA, 2019)
This study aims to find out and analyze the role of USG as well as to know and analyze legal determination ah iddah through USG in the perspective of Maqashid Syariah. This study is a library research (Library Research), in this study The type of data used in this study is a type of qualitative data. Based on the results of the author's research, it was concluded that the development of modern technology could not change the provisions of the short length of the Iddah period which had been determined and explained the Qur'an and Hadith. Although there is a belief that the divorced woman's womb is clean and between husband and wife it is impossible to reconcile. Thus, the problem of Iddah in Islamic teachings is ta'abbudi (devotion to Allah) and not ta'aqquli (cause and reason). At certain times when a woman who is divorced falls into the category of ‘Iddah who has an irregular menstrual cycle and a monopouse woman , herein lies the role of USG in determining the length of iddah time’s the woman is.